Puffy - Rolley, Anne-Maree; Novák, Jiří Tibor (Milsons Point, N.S.W. : Random House Australia, 1993)
The story of Puffy who cracks out of his egg on a smooth and warmish midsummer day and surprises everyone by wanting to hokey pokey.
"A Mark Macleod book".
For 4-8 year olds.
Keywords: Australian